Implementation Cashless Policy To Minimize Fraud in The Installment Payment - Hana, Choirul; Kusumawati, Yessy; Yoeli Astari, Ita (Universitas Nusantara PGRI Kediri, 2024)
Research aim: This study aims to identify fraud prevention strategies by implementing a cashless policy in the installment payment. Design/Method/Approach: To analyze the data and determine the relationship between the variables, OLS regression was used. Descriptive and inferential statistical information in the form of mean, standard deviation, Bi-variant correlation were the key guide in determining the relationship between the variables. The result of the ANOVA on the level of significance was used to decide on whether or not to accept the hypothesis formulated for this study. Research Finding: The result of this study is that installment payment system innovations have led to changes in payment options by switching to non-cash transactions that are safer, more effective, and efficient. Cashless payments can prevent corruption, such as money laundering, bribery, and commissions for services or procurement. Theoretical contribution/Originality: As a reference for further research. Practitionel/Policy implication: cashless transactionthat are safer, more effective and efficient, prevent corruption. Research limitation: Cashless Policy in the instalment payment.